Seasonal variations in levels of Heavy metals in muscles of crab Sesarma boulengeri collected from Al-Garaf canal at Thi Qar province, Iraq - A. Hussein, Sadek; K. Fahad, Kamel (University of Thi-Qar Journal of Science, 2019)
The present work is aiming at investigating seasonal variations in levels of some heavy metals (Ni, Cd, and Cu & Zn) in muscles of the crab Sesarma boulengeri. Samples were collected from Al-Garaf canal at Thi Qar governorate. The study extended from March 2004 to February 2005. Specimens were collected from a location supply cities of Basrah, Thi Qar, Shatra and Garaf water’s purification boards with crude freshwater for domestic uses. The surrounding areas are affected with sewage and agricultural disposals. It also represent mixing zone of water masses of various compositions. Elements found to vary seasonally in their levels and analyses of muscles indicate that Ni occupied the first position and revealed the highest levels, in general. The minimal recorded accumulative values (200.11 μg/g dry wt) was in Spring and the highest (243.20 μg/g dry wt) in summer. Zinc occupied second accumulation levels and showed the minimal (55.13 μg/g dry wt) in spring, whereas Cd, by no means, exhibited the minimal concentrations and the lowest value (4.82 μg/g dry wt) was in winter. Causes and effects of trace elements were discussed.